Optimization of total phenolic compounds extracted from propolis by ultrasound- assisted extraction - Najihah, Yusof; Mimi Sakinah, A. M.; Kutty, R. Veloo (Taylor & Francis, 2020)
The presence of phenolics in propolis contributes to several health benefits such as anti-microbial, antioxidant, anticancer, and anti-inflammatory properties. In this study, total phenolic compounds from propolis were extracted with the aid of sonication. The parameters screening was done by one factor at time (OFAT) which involved types of solvent, ethanol concentration, extraction temperature and extraction time. The highest total phenolic content obtained was at 80%, 25 minutes, 65 °C for ethanol concentration, extraction time and extraction temperature respectively. Optimization of the experimental parameters was done by applying response surface methodology (RSM). The best potential variation of the factors (X); ethanol concentration (X1), extraction temperature (X2) and extraction time (X3) was generated. The optimum conditions of the variables were 80% (X1), 25 min (X2) and 60 °C (X3). Under this setting, the phenolic content from the experimental work obtained was 0.1007 mg GAE/g of propolis, which complemented the predicted value.